PERAWATAN RUTIN EXCAVATOR EX2500-6 HITACHI JENIS BACKHOE - , ARIF DARMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT HEXINDO ADI PERKASA Tbk., is a company that move in sales and after sales service heavy equipment sector and one of the best distributor of heavy equipment in Indonesia that sell Hitachiâs product. Specifically for the Excavator EX 2500-6 type Backhoe. The unit of excavator and equipments itself have period in the used. Because of them for maximizing the service Hexindo must do periodically maintenance to prevent breakdown unit. The purpose of my final project is to study carefully about the maintenance in Hitachiâs Excavator EX2500-6 type backhoe. Daily maintenance and another periodic maintenance do after the unit operated for 250 hour, 500 hour, 1000 hour and 2000 hour. The conclusions of the daily maintenance in Hexindo for the each time maintenance hour is to keep ability of the unit excavator, the ability of excavator must in good condition to prevent for breakdown unit and there is a continuously. After the maintenance condition of unit and reduce some of the elements, it can be used like as the new product.